Developing a CRISPR/Cas9 Plasmid Vector Containing Specific Single Guide RNAs Targeting SMO in the Sonic Hedgehog Signaling Pathway for SHH-Driven Cancers. - Ghorbanlou, Mehrdad; Salimi-Jeda, Ali; Razavi, Mohamad Reza; Shabani, Ronak; Moradi, Fatemeh; Marzban, Hassan; Mehdizadeh, Mehdi (Journal of Advances in Medical & Biomedical Research)
Background & Objective: Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas) system is considered an efficient tool for genomic engineering in the field of cancer/gene therapy. Developing a plasmid vector to target the signaling pathway of sonic hedgehog (SHH), a key driver of malignancies such as medulloblastoma and basal cell carcinoma, is the aim of this study. Materials & Methods: CRISPOR online platform was used to select three specific and efficient gRNAs (guide RNAs) to design and then synthesize a gRNA cassette in a plasmid vector to target SHH pathway. Following digestion of pCas-guide-EF1aGFP, the Cas9 expressing vector, by BsrGI and BamHI restriction enzymes and ligation with T4 ligase, the gRNA cassette was cloned. After that, competent DH5α E. coli bacteria were used to amplificate the vector. Finally, after plasmid extraction, presence of the gRNA cassette was confirmed through DNA sequencing and polymerase chain reaction (PCR). Results: To target SMO gene, as an upstream target of SHH pathway, three targetprone exons (2nd, 4th, and 6th) were used to synthesize efficient and specific gRNAs. The process of cloning and developing the interested vector was confirmed by sequencing and PCR. Conclusion: Although this study lacks in vitro/in vivo validation of the candidate gRNAs within the plasmid vector, developing efficient, and specific CRISPR/Cas9 vectors may possibly be a promising approach in the field of cancer treatment through targeting neoplastic pathways at the level of positive regulators which may possibly lead to a better perception of different molecular pathways leading to cancer, and developing precise chemotherapeutic agents.